2019
DOI: 10.1111/1753-0407.12994
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a scoring model for differential diagnosis of diabetic nephropathy and nondiabetic renal diseases in type 2 diabetic patients

Abstract: Background We aim to design a scoring model for differential diagnosis between diabetic nephropathy (DN) and nondiabetic renal disease (NDRD) in type 2 diabetic patients through a combination of clinical variables. Methods A total of 170 patients with type 2 diabetes who underwent kidney biopsies were included and divided into three groups according to pathological findings: DN group (n = 46), MIX group (DN + NDRD, n = 54), NDRD group (n = 70). Clinical characteristics and laboratory data were collected and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Progression of T2DM, poor glycemic control, DR, deterioration of kidney function, hematuria, hypertension can guide to differentiation between DN and NDKD in many studies ( Li et al, 2020 ; Popa et al, 2021 ; Saini, Kochar & Poonia, 2021 ), which were consistent with our findings. Pallayova et al (2015) found that a strong predictor of NDKD was low serum HbA1c level.…”
Section: Discussionsupporting
confidence: 91%
“…Progression of T2DM, poor glycemic control, DR, deterioration of kidney function, hematuria, hypertension can guide to differentiation between DN and NDKD in many studies ( Li et al, 2020 ; Popa et al, 2021 ; Saini, Kochar & Poonia, 2021 ), which were consistent with our findings. Pallayova et al (2015) found that a strong predictor of NDKD was low serum HbA1c level.…”
Section: Discussionsupporting
confidence: 91%
“…The CNN model for detecting plants and flowers, was discussed in this article (Wassan et al, 2021). Li et al devise a scoring model to help patients with type 2 diabetes distinguish between diabetic nephropathy (DN) and non-diabetic renal disease (NDRD) (Li et al, 2020). In this study, the authors compare and contrast various machine learning-based classifiers.…”
Section: Bayes and Decision Trees For Dr Diagnosismentioning
confidence: 99%
“…Therefore, determining whether renal injury is associated with MIg holds considerable importance for treatment decisions and patient prognosis assessments. Although various prediction models have been employed for clinical prediction and prognostic assessment in various diseases 3 , 4 , prediction models for the diagnosis of MGRS lesions are notably absent in existing literature. There, in this study, we aimed to conduct a retrospective investigation into the correlation between clinical indicators and the diagnosis of MGRS lesions.…”
Section: Introductionmentioning
confidence: 99%